Chest tubes in COVID-19 times: a safe way to protect the team - Medeiros,Bruno José da Costa (2020)
SUMMARY INTRODUCTION What has been published so far regarding safe methods to deal with chest tube insertion during COVID-19. METHODS A descriptive study of the literature available in the Medline/PubMed, Lilacs, Scopus databases and specialized books. The search was carried out using the terms “infectious diseases”; “COVID-19”; “Chest tubes”. RESULTS This paper aggregates and consolidates some old concepts to new tactics to minimize the contamination of teams who deal with chest tubes, before, during, and after the procedure. CONCLUSIONS Health officials are under increasing pressure to control the spread of COVID-19, which is a very virulent disease. Our analysis brought together old rules against contamination along with new tactics for professionals who deal with chest drains in order to minimize the contamination of teams during the Pandemic.